Impact of Pre-Treatments and Processing on the Shelf Life Quality of Papaya Products - Sheeja N (Department of Home Science, College of Agriculture, 1994)
The present investigation was undertaken to study the influence of pretreatments and processing on the shelf-life quality of papaya products.